OLBCA: a new lightweight block cipher algorithm - AlDabbagh, Sufyan Salim Mahmood; Alshaikhli, Imad Fakhri Taha (2014)
Lightweight block cipher algorithms are vital for constrained environment. It is easy to propose an algorithm that optimize any two factors like (security and cost), (security and performance) and (cost and performance) but it is difficult to optimize three factors together at the same time. In this paper, we propose a new lightweight block cipher algorithm called OLBCA. PRESENT lightweight block cipher algorithm is chosen because it is one of the most common and famous lightweight algorithms. Also, the International Organization for Standardization and the International Electro technical Commission (ISO/IEC 29192-2:2012) declared that PRESENT as a new international standard for lightweight cryptographic methods. We applied three attacks differential, integral attacks and boomerang attack. The results showed that OLBCA is better than PRESENT algorithms in three factors.